Sodium–Glucose Cotransporter 2 Inhibitors in Heart Failure with Preserved Ejection Fraction: Rationale for and Practical Use of a Successful Therapy - Mauro Gori; Emilia D’Elia; Edoardo Sciatti; Michele Senni (Cardiac Failure Review)
Heart failure (HF) with preserved left ventricular ejection fraction is a common disease with a poor prognosis and rising prevalence in the community. The current paradigm of treatment includes symptomatic therapy, such as diuretics, and risk factor control and treatment of comorbidities. According to European guidelines, there is no effective therapy for patients with HF with left ventricular ejection fraction (LVEF) ≥50%, while drugs normally used in HF with reduced LVEF might also be effective for patients with mildly reduced LVEF (40–50%), with a IIB class of recommendation. The recently published EMPEROR-Preserved trial has challenged current guidelines, demonstrating improved outcomes in patients with HF and LVEF >40% with the sodium–glucose cotransporter 2 inhibitor (SGLT2I) empagliflozin, compared with placebo. This result was consistent in patients with and without diabetes as well as in those with LVEF below and above 50%. The authors describe the rationale for this therapy, presenting the main results of the EMPEROR-Preserved trial, and provide some recommendations for the everyday clinical management of HF with preserved left ventricular ejection with an SGLT2I.